Factors Influencing Family Support for Education Patterns in School-Age Children - Puspitarini, Nurul Aisyiyah; Kumboyono, Kumboyono; Hayati, Yati Sri (Universitas Aisyah Pringsewu, 2023)
Introduction: The family’s role in providing the child with education and supporting his/her success is critical. The relationship between the child and parenting behavior can affect the child’s achievements at school. Objective: Aimed to map and summarize critically the scientific evidence of the factors which influence family support for education patterns in school-age children. Method: A systematic search was carried out on five database PubMed, Science Direct, ProQuest, DOAJ, and search engine Google Scholar. Journal articles were extracted and selected under the PRISMA guide. Fifty-six journal articles were qualified based on the predetermined criteria. Results: The factors which influence family support for education patterns in school-age children identified in this scoping review include structural factors (family composition, the genders of the parents and the child, the social condition of the family and the child, the economic condition of the family and the child, and family education) and functional factors (family communication and the psychological conditions of the family and the child). The family and the child are an integral unity, and they support each other in education. Conclusions: Continuous support of the family for the education pattern of the school age child would shape the child’s behaviors and achievement’s. Abstrak: Latar Belakang: Pentingnya peran dari keluarga dalam memberikan pendidikan dan menunjang keberhasilan anak. Hubungan dari anak dan perilaku parenting dapat memberikan efek pada prestasi anak sekolah. Tujuan: untuk memetakan dan meringkas secara kritis terhadap bukti ilmiah tentang faktor yang mempengaruhi dukungan keluarga terhadap pola pendidikan pada anak usia sekolah. Metode: Pencarian sistematis dilakukan dari 5 database yaitu PubMed, Science Direct, ProQuest, dan DOAJ serta melalui mesin pencari, Google Scholar. Artikel jurnal diambil dan diseleksi dengan mengikuti pedoman PRISMA. Lima puluh enam artikel jurnal memenuhi syarat berdasarkan kriteria yang telah ditentukan sebelumnya. Hasil: Faktor yang mempengaruhi dukungan keluarga terhadap pola pendidikan pada anak usia sekolah yang didapatkan dari scoping review ini meliputi factor struktural (komposisi keluarga, jenis kelamin orangtua dan anak, sosial keluarga dan anak, ekonomi keluarga serta pendidikan keluarga) dan faktor fungsional (komunikasi keluarga serta psikologis keluarga dan anak). Keluarga dan anak merupakan satu kesatuan yang saling mendukung dalam pendidikan. Kesimpulan: Dukungan keluarga yang berkesinambungan terhadap pola pendidikan anak usia sekolah membentuk perilaku dan prestasi anak.